1991
DOI: 10.1016/0014-5793(91)80529-c
|View full text |Cite
|
Sign up to set email alerts
|

Duplication of leader sequence for protein targeting to mitochondria leads to increased import efficiency

Abstract: Wc descrtb~ a novel method for enhancinj protein import into mltochondria, by [andemly dup!icating the N.termi~al elc~tvabl© leader l~pttde usinll a llcnc manipuhttlon strategy. The import into i~olated >'east mitoehondria of On,senator proteins (yeast mitochondrial ATE syntha~ ~,~Jbunits 8 and 9 anti some mutalienised derivatives) that show little or no import when endowed with one such leader (that of Neuraspura cra#~a mitochon. drial ATE ~ynzhase subunit 91 is remarkably improved wt~en the leader is randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…The duplication of the MTS was found to improve the in vitro and in vivo import of hydrophobic proteins into yeast mitochondria (32,39). It was suggested that a long MTS can improve the interaction of the precursor with the mitochondrial import machinery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The duplication of the MTS was found to improve the in vitro and in vivo import of hydrophobic proteins into yeast mitochondria (32,39). It was suggested that a long MTS can improve the interaction of the precursor with the mitochondrial import machinery.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothetical boundary between importable and nonimportable proteins, indicated by a broad, gray diagonal, was derived from Claros et al (39) and Pérez-Martínez et al (11). The following proteins with their symbols were analyzed:…”
Section: Discussionmentioning
confidence: 99%
“…These multiple Tom20-recognition motifs could offer a second C-terminal Tom20-binding element, like the pSu9 presequence, to increase the import efficiencies. In this connection, it would be interesting to note that the presequence with a duplication of pSu9 further improved the import efficiency of mitochondrial precursor proteins (22). In order to further confirm that a second Tom20 binding element is not specific to the Su9 presequence, we picked up the presequence of Mprl3, a mitochondrial ribosomal protein of the large subunit 1, as one of the long presequences that was predicted to have second Tom20-binding elements.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that the N-terminal 13 residues (including the first Val) are essential for the biosynthesis of nosiheptide. Previous studies have shown that a tandem duplication of the mitochondrion-targeting leader sequence is capable of improving the efficiency of delivery of the protein into mitochondrial matrix (23). If the leader peptide was a target region for PTM enzymes, a tandem duplicated leader sequence would enhance the interaction between the precursor and PTM enzymes, which might be favorable to the posttranslational processing to produce nosiheptide.…”
Section: Resultsmentioning
confidence: 99%